Serum Cannabinoid 24 h and 1 Week Steady State Pharmacokinetic Assessment in Cats Using a CBD/CBDA Rich Hemp Paste - Wang, Tongxin; Zakharov, Alex; Gomez, Beatriz; Lyubimov, Alex; Trottier, Nathalie L.; Schwark, Wayne S.; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2022)
Hemp based cannabinoids have gained popularity in veterinary medicine due to the potential to treat pain, seizure disorders and dermatological maladies in dogs. Cat owners are also using hemp-based products for arthritis, anxiety and neoplastic disorders with no studies assessing hemp cannabinoids, namely cannabidiol efficacy, for such disorders. Initial twenty-four pharmacokinetic and chronic dosing serum concentration in cats are sparse. The aim of our study was to assess 8 cats physiological and 24 h and 1-week steady state pharmacokinetic response to a cannabidiol (CBD) and cannabidiolic acid (CBDA) rich hemp in a palatable oral paste. Using a standard dose of paste (6.4 mg/CBD + CBDA 5.3 mg/gram) across 8 cats weighing between 4.2 and 5.4 kg showed an average maximal concentration of CBD at 282.0 ± 149.4 ng/mL with a half-life of ~2.1 ± 1.1 h, and CBDA concentrations of 1,011.3 ± 495.4 ng/mL with a half-life of ~2.7 ± 1.4 h, showing superior absorption of CBDA. After twice daily dosing for 1 week the serum concentrations 6 h after a morning dosing showed that the acidic forms of the cannabinoids were approximately double the concentration of the non-acidic forms like CBD and Δ9- tetrahydrocannabinol (THC). The results of this study compared to two other recent studies suggest that the absorption in this specific paste product may be superior to oil bases used previously, and show that the acidic forms of cannabinoids appear to be absorbed better than the non-acidic forms. More importantly, physical and behavioral examinations every morning after dosing showed no adverse events related to neurological function or behavioral alterations. In addition, bloodwork after 1 week of treatment showed no clinically significant serum biochemical alterations as a reflection of hepatic and renal function all remaining within the reference ranges set by the diagnostic laboratory suggesting that short-term treatment was safe.